Synthesis, structural, and magnetic characterization of linear and bent geometry cobalt(II) and nickel(II) amido complexes: evidence of very large spin-orbit coupling effects in rigorously linear coordinated Co2 - Bryan, Aimee M; Merrill, W Alexander; Reiff, William M; Fettinger, James C; Power, Philip P (Inorganic chemistry, 2012)
The complexes M(II){N(H)Ar(Pr(i)(6))}(2) (M = Co, 1 or Ni, 2; Ar(Pr(i)(6)) = C(6)H(3)-2,6(C(6)H(2)-2,4,6-Pr(i)(3))(2)), which have rigorously linear, N-M-N = 180°, metal coordination, and M(II){N(H)Ar(Me(6))}(2) (M = Co, 3 or Ni, 4; Ar(Me(6)) = C(6)H(3)-2,6(C(6)H(2)-2,4,6-Me(3))(2)), which have bent, N-Co-N = 144.1(4)°, and N-Ni-N = 154.60(14)°, metal coordination, were synthesized and characterized to study the effects of the metal coordination geometries on their magnetic properties. The magnetometry studies show that the linear cobalt(II) species 1 has a very high ambient temperature moment of about 6.2 μ(B) (cf. spin only value = 3.87 μ(B)) whereas the bent cobalt species 3 had a lower μ(B) value of about 4.7 μ(B). In contrast, both the linear and the bent nickel complexes 2 and 4 have magnetic moments near 3.0 μ(B) at ambient temperatures, which is close to the spin only value of 2.83 μ(B). The studies suggest that in the linear cobalt species 1 there is a very strong enhanced spin orbital coupling which leads to magnetic moments that broach the free ion value of 6.63 μ(B) probably as a result of the relatively weak ligand field and its rigorously linear coordination. For the linear nickel species 2, however, the expected strong first order orbital angular momentum contribution does not occur (cf. free ion value 5.6 μ(B)) possibly because of π bonding effects involving the nitrogen p orbitals and the d(xz) and d(yz) orbitals (whose degeneracy is lifted in the C(2h) local symmetry of the Ni{N(H)C(ipso)}(2) array) which quench the orbital angular momentum.